Evaluation Of Drug Storage System In A Pharmacy Of Medan City Based On Pharmaceutical Services Standards - Rinda Sari, Syilvi; Yunus, Muhammad; Rawitri, Kiki; Wahyuni, Sri; Rani, Zulmai; Syahputri, Hindri (Publisher Cv. Inara, 2023)
Pharmacy is a place where pharmaceutical services are held by pharmacists who are responsible for patients. Pharmaceutical services in pharmacies are related to drugs with the aim of achieving definite results to improve the quality of life of patients. So the management of drugs in pharmacies needs to be done properly and precisely to ensure the availability of sufficient and quality drugs in order to achieve optimal service goals by implementing a storage system that is in accordance with pharmaceutical service standards no.73 of 2016. Therefore the purpose of this research is to evaluate the drug storage system in one of the Medan city pharmacies based on pharmaceutical service standards. This research is descriptive with retrospective data collection. The data obtained were grouped into quantitative data presented in tabular form to see visual comparisons, and qualitative data obtained through observation and interviews with informants. The results showed that in several indicators of drug storage in one of the Medan city pharmacies based on Permenkes No. 73 of 2016 there are still those that have not complied with, namely in the preparation of LASA drugs and writing document numbers on drug stock cards. Meanwhile, the standard drug storage indicators are the columns on the stock card consisting of receipt or dispensing date, receipt or disbursement document number, source of origin of the drug, no. batch/no. Lot, expiry date, receipt and disbursement amount, remaining stock, and officer's initials, as well as suitability for drug storage based on dosage form, alphabetical order, and FEFO and FIFO storage methods. Based on the results of the study it was concluded that the drug storage system carried out in one of the pharmacies in the city of Medan did not meet pharmaceutical service standards based on Permenkes No. 73 of 2016.